COP1 Controls Abiotic Stress Responses by Modulating AtSIZ1 Function through Its E3 Ubiquitin Ligase Activity - Kim, Joo Y.; Jang, In-Cheol; Seo, Hak S. (Frontiers in Plant Science, 2016)
Ubiquitination and sumoylation are essential post-translational modifications that regulate growth and development processes in plants, including control of hormone signaling mechanisms and responses to stress. This study showed that COP1 (Constitutive photomorphogenic 1) regulated the activity of Arabidopsis E3 SUMO (Small ubiquitin-related modifier) ligase AtSIZ1 through its E3 ubiquitin ligase activity. Yeast two hybrid analysis demonstrated that COP1 and AtSIZ1 directly interacted with one another, and subcellular localization assays indicated that COP1 and AtSIZ1 co-localized in nuclear bodies. Analysis of ubiquitination showed that AtSIZ1 was polyubiquitinated by COP1. The AtSIZ1 level was higher in cop1-4 mutants than in wild-type seedlings under light or dark conditions, and overexpression of a dominant-negative (DN)-COP1 mutant led to a substantial increase in AtSIZ1 accumulation. In addition, under drought, cold, and high salt conditions, SUMO-conjugate levels were elevated in DN-COP1-overexpressing plants and cop1-4 mutant plants compared to wild-type plants. Taken together, our results indicate that COP1 controls responses to abiotic stress by modulation of AtSIZ1 levels and activity.